2015
DOI: 10.1155/2015/957031
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Fraction of Orange and Bergamot Juices Protect Human Lung Epithelial Cells from Hydrogen Peroxide-Induced Oxidative Stress

Abstract: It has been reported that oxidant/antioxidant imbalance triggers cell damage that in turn causes a number of lung diseases. Flavonoids are known for their health benefits, and Citrus fruits juices are one of the main food sources of these secondary plant metabolites. The present study was designed to evaluate the effect of the flavonoid fraction of bergamot and orange juices, on H2O2-induced oxidative stress in human lung epithelial A549 cells. First we tested the antioxidant properties of both extracts in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 59 publications
(67 reference statements)
6
61
0
Order By: Relevance
“…In addition, although natural remedies are not risk free, they are generally safer than both synthetic and biological drugs. In this context, we have recently shown that BJe has antioxidant properties [235,236] and is able to suppress pro-inflammatory responses in both in vitro [237,238] and in vivo models [239,240]. Interestingly, evidence showing that BJ did not significantly affect the viability of normal human diploid fibroblast WI-38 cells [229], as well as not provoking any apparent sign of systemic toxicity [231], together with its antimicrobial activity [241,242] and favorable safety/efficacy balance [243], reveals the potential of BJe as an anti-cancer remedy, highlighting that it could represent a novel strategic approach in oncology field.…”
Section: Anti-cancer Properties Of Citrus Juices and Extractsmentioning
confidence: 99%
“…In addition, although natural remedies are not risk free, they are generally safer than both synthetic and biological drugs. In this context, we have recently shown that BJe has antioxidant properties [235,236] and is able to suppress pro-inflammatory responses in both in vitro [237,238] and in vivo models [239,240]. Interestingly, evidence showing that BJ did not significantly affect the viability of normal human diploid fibroblast WI-38 cells [229], as well as not provoking any apparent sign of systemic toxicity [231], together with its antimicrobial activity [241,242] and favorable safety/efficacy balance [243], reveals the potential of BJe as an anti-cancer remedy, highlighting that it could represent a novel strategic approach in oncology field.…”
Section: Anti-cancer Properties Of Citrus Juices and Extractsmentioning
confidence: 99%
“…Bergamot juice (BJ) has always been considered a by‐product, yet in the last decade, the beneficial effects of its flavonoid‐rich extract (BJe) have been highlighted by several studies (Cirmi et al, ; Ferlazzo, Cirmi, Calapai, et al, ; Mannucci et al, ). Its antioxidant (Ferlazzo et al, ; Ferlazzo, Visalli, Cirmi, et al, ), anti‐inflammatory (Curro et al, ; Impellizzeri et al, ; Impellizzeri et al, ; Risitano et al, ), anticancer (Delle Monache et al, ; Ferlazzo, Cirmi, Russo, et al, ; Navarra et al, ; Visalli et al, ), and antimicrobial (Filocamo et al, ) properties have been reported. Regarding the anti‐inflammatory effect exerted by BJe, we showed that, in acute leukemic monocytes THP‐1 stressed with lipopolysaccharide (LPS), it is mediated by the activation of SIRT1, which in turn inhibited the activation of NF‐κB (Risitano et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The LDH release was accompanied by a significant increase in cell death, as detected by flow cytometry through a propidium iodide assay (Fig. 8) [5051]. …”
Section: Resultsmentioning
confidence: 99%